Characterization and reduction of the amplitude-to-phase conversion effects in telemetry. (1st July 2015) - Guillory, J; García-Márquez, J; Alexandre, C; Truong, D; Wallerand, J-P
Abstract: We are developing a telemeter based on the measurement of the phase accumulated by an RF sine wave during its propagation in air. This wave is carried by a laser beam by an intensity modulation. The main limitation of this technique lies in amplitude-to-phase conversion occurring in the detection of this modulation. Therefore, we characterize this phenomenon for a given telemetric system and discuss how to reduce its effects on the resolution and the accuracy of the distance measurement. Finally, a solution is implemented and tested outdoors in real conditions of use.